As mais belas máquinas - ed. lit. Abril/ Control Jornal (Abril/Control Jornal, 1997)
1.º vol.: Os primódios, 64 p.; 2.º vol.: Década de 50, 64 p.; 3.º vol.: Década de 60, 64 p.; 4.º vol.: Década de 70, 64 p.; 5.º vol.: Década de 80, 64 p.; 6.º vol.: Década de 90, 64 p.